Coexistence of EGFR, KRAS, BRAF, and PIK3CA Mutations and ALK Rearrangement in a Comprehensive Cohort of 326 Consecutive Spanish Nonsquamous NSCLC Patients - Martín Martorell, Paloma; Huerta, Marisol; Compañ Quilis, Amparo; Abellán, Rosario; Seda, Enrique; Blesa, Sebastián; Chaves, Felipe J.; Dualde Beltrán, Diego; Roselló Keränen, Susana; Franco, José; Insa, Amelia (Clinical lung cancer, 2017)
Molecular information from 326 nonsquamous non–small-cell lung cancer patients is presented with the aim of determining driver mutation coexistence and response to treatment. To the best of our knowledge, limited data have been presented on this subject. We found a 12% rate of mutational coexistence using next-generation sequencing and anaplastic lymphoma kinase immunohistochemical analysis. Most cases with coexisting mutations did not respond well to targeted treatment. Molecular screening is crucial for the care of nonsquamous non–small-cell lung cancer (NSCLC) patients. The coexistence of mutations could have important consequences regarding treatment. We described the mutational patterns and coexistence among patients and their outcomes after targeted treatment. Data from consecutive patients with newly diagnosed nonsquamous NSCLC were prospectively collected. Next-generation sequencing analysis of mutational hotspots in the EGFR, KRAS, PIK3CA, and BRAF genes and analysis of anaplastic lymphoma kinase (ALK) rearrangement were performed. A total of 326 patients with nonsquamous NSCLC were identified. Of the 326 patients, 240 (73.6%) had EGFR, 141 (43.3%) KRAS, 137 (42.0%) BRAF, 130 (39.9%) PIK3CA mutation and 148 (45.4%) ALK rearrangement determined. Of the 240 with EGFR determination, 24.1% harbored EGFR mutations. Of these, 16.3% were activating mutations (43.6%, exon 19 deletion; 46.1%, exon 21; and 10.3%, exon 18) and 7.9% were nonsensitizing EGFR mutations. Furthermore, 39.0% had KRAS mutations, 2.9% BRAF mutations, 10.0% PIK3CA mutations, and 8.8% ALK rearrangements. Of the 154 stage IV patients with ≥ 1 mutations, analysis showed 19 coexisting cases (12.3%). Of 8 patients receiving targeted treatment, 6 had no response. Both responders to targeted treatment had coexistent PIK3CA mutations. Driver mutations can coexist in nonsquamous NSCLC. In our cohort, 12.3% of cases with stage IV disease had multiple mutations. Targeted treatment might not be as effective in patients with coexisting mutations; however, coexistence with PIK3CA might not preclude a response.